A bioareactor based on optical measurements for Baker's yeast fermentation - Soares, Filomena (2002)
This paper presents a bioreactor for baker’s yeast fermentation. Small volumes are used in the bioreactor (< 100 ml) comparing with the macro setup (5 l). Biomass, ethanol and pH measurements are carried out by optical spectral analysis: the first two by optical absorption method and the last one is determined by fluorescence. HPTS (8 Hydroxypyrene-1,3,6-trisulfonic acid Trisodium salt) is chosen for pH measurement due to be the most suitable for precise and stable pH analysis (aqueous acid/base, biomass, ethanol and glucose solutions). A resolution of 0.2 in pH scale was achieved. Known biomass concentrations are measured with a stable pH=4 (no interference between the two measurements). Design and implementation of a bioreactor-on-a-chip for baker’s yeast fermentation is the final goal of this study.